A Benefit-Focused Analysis of Constitutional Health Rights - Pieterse, Marius (My University, 2006)
Socio-economic rights have the potential to contribute to the achievement of social justice through insisting on the satisfaction of vital material needs. However, their effectiveness in this regard is compromised when they are incapable of tangibly contributing to the satisfaction of the needs that they represent. By including justiciable socio-economic rights in the text of the 1996 South African Constitution, its drafters indicated that South Africans are entitled to demand effective relief that amounts to adequate reparation for the harm suffered through the non-satisfaction of their vital material needs. The legitimacy of the constitutional order partially depends on the ability of socio-economic rights to live up to this promise. This dissertation examines the extent of this promise and the extent to which it is currently being fulfilled, in relation to a discrete set of rights - those that operate together to achieve the highest attainable standard of physical and mental health. I argue that successful reliance on healthrelated rights in litigation must, in appropriate circumstances, produce tangible benefits for individual rights-bearers. I explore the extent to which constitutional health rights may realistically be expected to render tangible benefits, examine the degree to which this potential of health rights is realised through current judicial approaches to their vindication and suggest manners in which such approaches may be modified and/or supplemented in order for tangible benefits to result more readily from successful vindication of health rights. In doing this, I attempt to show that a benefit-orientated approach to the interpretation and enforcement of health rights is not only required, but also facilitated by the Bill of Rights in the 1996 Constitution. Moreover, the Bill of Rights enables South African courts to interpret and enforce health rights in accordance with their benefit-rendering potential, without overextending judicial capabilities or transgressing the institutional boundaries of the judicial function. Courts are accordingly implored to acknowledge and affirm the justiciable nature of healthrelated rights and to adopt interpretative, evaluative and remedial practices that enable their tangible vindication in appropriate circumstances.
Student Number : 0215058X - PhD thesis - School of Law - Faculty of Commerce, Law and Management
Keywords: constitution; health care; socio-economic rights; right ot health; adjudication